2019
DOI: 10.3928/23258160-20181212-05
|View full text |Cite
|
Sign up to set email alerts
|

Culture-Proven Endophthalmitis After Intravitreal Injection: A 10-Year Analysis

Abstract: BACKGROUND AND OBJECTIVE: To report on the microbiology, management, and visual outcomes of intravitreal injection (IVI)-associated, culture-proven endophthalmitis. PATIENTS AND METHODS: All patients seen at a tertiary referral center with culture-proven endophthalmitis associated with an IVI between June 2007 and July 2017 were included in this retrospective analysis. RESULTS: Thirty-five pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 37 publications
0
13
1
Order By: Relevance
“…Prior studies have demonstrated that oral Streptococcus species bacteria are commonly isolated in cases of endophthalmtis 18,19 and may be associated with worse visual outcomes in cases of intravitreal injectionrelated endophthalmitis. 20 In our cohort, culture-positive cases associated with oral flora trended toward worse presenting VA; however, these cases had similar VA at 6 months compared with other culture-positive cases. We did not observe a significant difference in initial VA or VA at 6 months between culture-positive and culture-negative cases.…”
Section: Discussionmentioning
confidence: 46%
“…Prior studies have demonstrated that oral Streptococcus species bacteria are commonly isolated in cases of endophthalmtis 18,19 and may be associated with worse visual outcomes in cases of intravitreal injectionrelated endophthalmitis. 20 In our cohort, culture-positive cases associated with oral flora trended toward worse presenting VA; however, these cases had similar VA at 6 months compared with other culture-positive cases. We did not observe a significant difference in initial VA or VA at 6 months between culture-positive and culture-negative cases.…”
Section: Discussionmentioning
confidence: 46%
“…Similar to post-cataract surgery infection, the most common microorganism isolated in culture proven IRE is coagulase-negative Staphylococcus [ 30 , 51 ]. Other less common organisms including Streptococcus species , Staphylococcus aureus , Haemophilus influenzae , Enterococcus faecalis , and Bacillus species have been reported [ 52 ]. In 2016, a retrospective analysis reported isolated rare microorganisms like Corynebacterium , Escherichia coli , Neisseria , Enterobacter cloacae , and Lactococcus garvieae as causes [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have found that IRE cases associated with Streptococcal species found in oropharyngeal flora ( S. viridans and S. pyogenes ) present earlier, follow a more aggressive course, and are associated with worse visual outcomes [ 51 , 53 , 54 ] (Table 1 ). In line with this association, a retrospective analysis conducted over a period of 10 years demonstrated that due to the severity of clinical presentation, patients with endophthalmitis due to Streptococcus species were more likely to require vitrectomy surgery as part of their management and had worse visual outcomes [ 52 ]. In a retrospective case series conducted by Goldberg et al, an outbreak of infection caused by Streptococcus mitis/oralis resulted in 7 of 12 patients (58%) requiring enucleation or evisceration by 1 year follow-up [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…7 Among these, endophthalmitis caused by the Streptococcus viridans species may progress more rapidly and result in worse visual outcomes. 3,18,19 While nearly all cases of presumed infectious endophthalmitis following intravitreal injection are managed with broadspectrum intravitreal antimicrobials, such as vancomycin and ceftazidime, precise treatment guidelines have not been well established. 2,19 As such, diagnostic and management decisions are often extrapolated from results of the Endophthalmitis Vitrectomy Study (EVS), which examined only cases of endophthalmitis following cataract surgery or secondary intraocular lens placement.…”
Section: Introductionmentioning
confidence: 99%
“…7 Among these, endophthalmitis caused by the Streptococcus viridans species may progress more rapidly and result in worse visual outcomes. 3,18,19…”
Section: Introductionmentioning
confidence: 99%